“Nós que aqui estamos por vós esperamos”: estudo sobre a conservação do patrimônio histórico no Cemitério Vera Cruz, Passo Fundo/RS - Galvan, Ana Carolina Lorenzet (2019)
This work aims to discuss heritage preservation and interventions in the cemetery space, taking the Vera Cruz Cemetery as its field of study. Inserted within the scope of Cultural History, the work seeks in its three chapters to contextualize the history of death in the West, so that it is possible to think about the symbolic and allegorical representations present in the cemetery space. Furthermore, there was a discussion about the preservation of funerary heritage, as well as possibilities for intervention in it, considering that, if done in line with historical research, it helps in the maintenance and enhancement of heritage.